Using Webb's model in alignment analysis of social studies curriculum standards and assessments - Falguera, Rosario Elena R. (College of Education, University of the Philippines Diliman, 2020)
This study used Norman Webb's model in alignment analysis of the standards of intended grades 4, 5, and 6 Araling Panlipunan curriculum and in-school assessments of a private catholic school. This study employed qualitative research through document analysis and quantified coding to interpret the degree of alignment of curriculum standards and in-school assessments of Araling Panlipunan 4, 5, and 6 according to the proposed degree of alignment of Webb's alignment model. To ensure this, a computer automated Web alignment tool (WATv2) was used as the primary instrument to gather data. Content experts familiar with the general content and competencies of Araling Panlipunan 4, 5, and 6 were invited to serve as expert reviewers and underwent two parts of the review process. The review process generated alignment results based on the four criteria for alignment under the content focus dimension of the model: categorical concurrence, depth-of-knowledge consistency, range of knowledge correspondence, and balance of representations. In conclusion, the Webb alignment model with its corresponding online tool, WATv2, is useful and applicable in comparing alignment of standards of grade 4, 5, and 6 Araling Panlipunan based on the four criteria for alignment proposed by the model.